Wiper blade rubber strip

CN122995980APending Publication Date: 2026-10-27BANDO CHEM IND LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580023269.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-22
Filing Date
2025-03-06
Publication Date
2026-10-27

Smart Images

  • Figure CN122995980A_ABST
    Figure CN122995980A_ABST
Patent Text Reader

Abstract

The wiper blade rubber (10) is formed of a crosslinked rubber composition containing a rubber component and carbon black. The carbon black has a nitrogen adsorption specific surface area of 20 m 2 / g or more and 40 m 2 / g or less. The content of the carbon black in the crosslinked rubber composition is 15 parts by mass or more and less than 30 parts by mass with respect to 100 parts by mass of the rubber component. The tensile permanent elongation of the crosslinked rubber composition is 12% or more and 18% or less, the 100% modulus S 100 of the crosslinked rubber composition is 1.9 MPa or more and 3 MPa or less, and the 10% modulus S 10 of the crosslinked rubber composition is 0.1 MPa or more and 0.4 MPa or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a wiper blade rubber strip. Background Technology

[0002] Crosslinked rubber compositions containing carbon black (SRF) are known as crosslinked rubber compositions for wiper blade rubber strips. For example, Patent Document 1 discloses a crosslinked rubber composition for wiper blade rubber strips containing 40 to 80 parts by weight of SRF relative to 100 parts by weight of the rubber component EPDM. Patent Document 2 discloses a crosslinked rubber composition for wiper blade rubber strips containing 30 parts by weight of SRF relative to 100 parts by weight of the rubber component CR. Patent Document 3 discloses a crosslinked rubber composition containing 50 parts by weight of SRF relative to 100 parts by weight of the rubber component EPDM.

[0003] Existing technical documents Patent documents Patent Document 1: Japanese Patent No. 6371900 Patent Document 2: Japanese Patent No. 5729877 Patent document 3: Japanese Patent Application Publication No. 2012-140090. Summary of the Invention

[0004] This invention relates to a wiper blade rubber strip, which is formed from a cross-linked rubber composition containing rubber components and carbon black, wherein the carbon black has a nitrogen adsorption specific surface area of ​​20 m². 2 / g or more and 40m 2 The carbon black content in the crosslinked rubber composition is 15 parts by weight or more and less than 30 parts by weight relative to 100 parts by weight of the rubber component, the permanent elongation at break of the crosslinked rubber composition is 12% or more and less than 18%, and the 100% modulus S of the crosslinked rubber composition is... 100 The crosslinked rubber composition has a 10% modulus S of 1.9 MPa or higher and 3 MPa or lower. 10 It is above 0.1 MPa and below 0.4 MPa. Attached Figure Description

[0005] Figure 1 This is a perspective view of one piece of the wiper blade rubber strip involved in the embodiment. Detailed Implementation

[0006] The implementation method will now be described in detail.

[0007] Figure 1 The wiper blade rubber strip 10 according to the embodiment is shown.

[0008] The wiper blade rubber strip 10 involved in the embodiment is a generally flat, slender rubber component. It has an H-shaped mounting and retaining portion 11 on one side in the width direction, a generally triangular lip 12 on the other side in the width direction, and a relatively thin neck 13 connected to the mounting and retaining portion and the lip.

[0009] The wiper blade rubber strip 10 according to the embodiment is such that the mounting and holding part 11 is mounted and held on the frame of the wiper drive unit, for example, provided on the lower side of the windshield of a car. When the wiper drive unit is working, the lip 12 tilts with the neck 13 as the fulcrum, and the edge 14 of the top of the lip 12 slides in contact with the surface of the windshield, thereby wiping away rainwater and the like.

[0010] The wiper blade rubber strip 10 involved in the embodiment is made of rubber components and has a nitrogen adsorption specific surface area of ​​20m². 2 / g or more and 40m 2 A crosslinked rubber composition (hereinafter referred to as "crosslinked rubber composition X") is formed from carbon black (hereinafter referred to as "carbon black A") of less than / g.

[0011] Examples of rubber components include natural rubber (NR), chloroprene rubber (CR), ethylene propylene diene monomer (EPDM), and styrene-butadiene rubber (SBR). Examples of CR include sulfur-modified, thiol-modified, and xanthic acid-modified types. The rubber component preferably contains one or more of these components, and from the viewpoint of suppressing deformation when exposed to high temperatures, a blend of NR and CR is more preferred.

[0012] When the rubber component contains NR, from the viewpoint of suppressing deformation when exposed to high temperatures, the Mooney viscosity of NR is preferably 50 ml. 1+4 (100℃ or above) and 80ML 1+4 (At 100°C or below), 55 ml is more preferred. 1+4 (100℃ or above) and 65ML 1+4 Below 100°C. This Mooney viscosity was measured based on Japanese Industrial Standard JIS K6300-1:2013 (the same applies below).

[0013] When the rubber component contains CR, from the viewpoint of suppressing deformation when exposed to high temperatures, the CR is preferably thiol-modified. From the same viewpoint, the Mooney viscosity of the CR is preferably 40 mL. 1+4 (100℃ or above) and 60ML 1+4 (At 100°C or below), 45 ml is more preferred. 1+4 (100℃ or above) and 53ML 1+4 (100℃) or less.

[0014] When the rubber component is a blend of NR and CR, from the viewpoint of suppressing deformation when exposed to high temperatures, it is preferable that the NR content is higher than the CR content. From the same viewpoint, the mass ratio of NR content to CR content (NR / CR) is preferably greater than 50 / 50 and less than 70 / 30, more preferably greater than 55 / 45 and less than 65 / 35.

[0015] As for carbon black A, examples include SRF (Semi-Reinforcing Furnace, ASTM N700 series, with a nitrogen adsorption surface area of ​​27 m²). 2 / g), GPF (General Purpose Furnace Black, ASTM N600 series, nitrogen adsorption specific surface area is 27m²). 2 Carbon black A preferably contains SRF and / or GPF, and from the viewpoint of suppressing deformation when exposed to high temperatures, it is more preferably found to contain SRF. These nitrogen adsorption specific surface areas were measured based on Japanese Industrial Standard JIS K6217-2:2017.

[0016] The nitrogen adsorption specific surface area of ​​carbon black A is 20 m². 2 / g or more and 40m 2 From the viewpoint of suppressing deformation when exposed to high temperatures, a value of 25m or less is preferred. 2 / g or more and 30m 2 / g or less.

[0017] From the viewpoint of suppressing curing in a low-temperature atmosphere, the arithmetic mean particle size of carbon black A is preferably 50 nm or more and 100 nm or less, more preferably 65 nm or more and 70 nm or less. This arithmetic mean particle size is determined by observing the carbon black using an electron microscope. Carbon black forms an aggregate structure of interconnected microparticles. The particle size here is the primary particle size calculated by approximating its diameter as a circle, treating the microparticle portion as a single particle (primary particle). This primary particle size is calculated by taking an electron microscope image of the carbon black and approximating it as a circle. Furthermore, the arithmetic mean particle size dn is the average of the primary particle sizes and is obtained by dn = (Σnidi) / (Σni).

[0018] The content of carbon black A in the crosslinked rubber composition X is 15 parts by mass or more and less than 30 parts by mass relative to 100 parts by mass of the rubber component. From the viewpoint of suppressing deformation when exposed to high temperatures, it is preferably 20 parts by mass or more and 29 parts by mass or less, more preferably 22 parts by mass or more and 28 parts by mass or less, and even more preferably 24 parts by mass or more and 28 parts by mass or less. It should be noted that, in this application, the content in the crosslinked rubber composition X refers to the amount incorporated into the uncrosslinked rubber composition X' before the crosslinked rubber composition X crosslinks.

[0019] The crosslinked rubber composition X may also contain vulcanization accelerators, processing aids, vulcanization accelerators, anti-aging agents, etc., as rubber compounding agents.

[0020] Examples of vulcanization accelerators include zinc oxide (zinc white), magnesium oxide and other metal oxides, metal carbonates, fatty acids and their derivatives. The vulcanization accelerator preferably contains one or more of these substances. From the viewpoint of suppressing deformation when exposed to high temperatures, it is more preferable to contain metal oxides, further preferably to contain zinc oxide and / or magnesium oxide, and even more preferably to contain both zinc oxide and magnesium oxide. It should be noted that when the rubber component contains CR and the vulcanization accelerator contains metal oxides, the metal oxides also function as crosslinking agents for CR.

[0021] The content of the vulcanization accelerator in the crosslinked rubber composition X is preferably 5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the rubber component.

[0022] Examples of processing aids include stearic acid, polyethylene wax, and metal salts of fatty acids. It is preferable that the processing aid contains one or more of these, and from the viewpoint of suppressing deformation when exposed to high temperatures, stearic acid is more preferably included. From the same viewpoint, the content of the processing aid in the crosslinked rubber composition X is preferably 0.5 parts by mass or more and 1.5 parts by mass or less per 100 parts by mass of the rubber component.

[0023] Examples of vulcanization accelerators include sulfenamide vulcanization accelerators, thiourea vulcanization accelerators, aldehyde-amine vulcanization accelerators, guanidine vulcanization accelerators, thiazole vulcanization accelerators, thiuram vulcanization accelerators, and dithiocarbamate vulcanization accelerators. The vulcanization accelerator preferably contains one or more of these types. From the viewpoint of suppressing deformation when exposed to high temperatures, it is more preferable to contain a sulfenamide vulcanization accelerator, and even more preferably, it contains a thiourea vulcanization accelerator in addition to a sulfenamide vulcanization accelerator. From the same viewpoint, the sulfenamide vulcanization accelerator preferably contains N-oxodiethylene-2-benzothiazole sulfenamide and / or N-tert-butyl-2-benzothiazole sulfenamide, and more preferably N-oxodiethylene-2-benzothiazole sulfenamide.

[0024] The content of the vulcanization accelerator in the crosslinked rubber composition X is preferably 2 parts by mass and 5 parts by mass or less, more preferably 3 parts by mass and 4 parts by mass or less, relative to 100 parts by mass of the rubber component. When the vulcanization accelerator contains both sulfenamide-based vulcanization accelerators and thiourea-based vulcanization accelerators, from the same viewpoint as above, it is preferable that the content of the sulfenamide-based vulcanization accelerator is greater than the content of the thiourea-based vulcanization accelerator. From the same viewpoint as above, the mass ratio of the content of the sulfenamide-based vulcanization accelerator to the content of the thiourea-based vulcanization accelerator is preferably 1 or more and 5 or less, more preferably 2 or more and 4 or less.

[0025] Examples of anti-aging agents include p-phenylenediamine, diphenylamine, amine-ketone, monophenol, bisphenol, polyphenol, benzimidazole, dithiocarbamate, phosphorous acid, and organothioic acid anti-aging agents. One or more of these agents can be added.

[0026] Preferably, the crosslinked rubber composition X is formed by crosslinking with sulfur as a crosslinking agent. In this case, the amount of sulfur in the uncrosslinked rubber composition X' is preferably more than 1 part by mass and less than 4 parts by mass relative to 100 parts by mass of the rubber component. It should be noted that the crosslinked rubber composition X may also be formed by crosslinking with an organic peroxide as a crosslinking agent.

[0027] Regarding the wiper blade rubber strip 10 according to the embodiment, the tensile permanent elongation of the crosslinked rubber composition X forming the wiper blade rubber strip 10 is 12% or more and 18% or less. From the viewpoint of suppressing deformation when exposed to high temperatures, it is preferably 16% or less, and more preferably 14% or less. This tensile permanent elongation is measured based on Japanese Industrial Standard JIS K6273:2018 at a standard test temperature (23±2°C).

[0028] The 100% modulus S of the crosslinked rubber composition X 100 The crosslinked rubber composition X has a strength of 1.9 MPa or higher and 3 MPa or lower. From the viewpoint of suppressing deformation when exposed to high temperatures, it is preferably 2.0 MPa or higher and 2.8 MPa or lower, and more preferably 2.3 MPa or higher and 2.6 MPa or lower. The 10% modulus S of the crosslinked rubber composition X is... 10 The pressure is 0.1 MPa or higher and 0.4 MPa or lower. From the same viewpoint as above, it is preferably 0.15 MPa or higher and 0.37 MPa or lower, and more preferably 0.3 MPa or higher and 0.35 MPa or lower. The 100% modulus S mentioned above... 100 and 10% modulus S 10 It was measured at the standard test temperature (23±2℃) according to Japanese Industrial Standard JIS K6251:2017.

[0029] According to the wiper blade rubber strip 10 of the above embodiment, by forming the wiper blade rubber strip 10 from the following crosslinked rubber composition, deformation when exposed to high temperature can be suppressed: the crosslinked rubber composition contains 15 parts by mass and less than 30 parts by mass of carbon black A relative to 100 parts by mass of rubber components, and the nitrogen adsorption specific surface area of ​​the carbon black A is 20 m². 2 / g or more and 40m 2 The crosslinked rubber composition has a tensile permanent elongation of 12% or more and 18% or less per g, and a 100% modulus S of the crosslinked rubber composition. 100 The 10% modulus S of the crosslinked rubber composition is above 1.9 MPa and below 3 MPa. 10 It is above 0.1 MPa and below 0.4 MPa.

[0030] A rubber compounding agent containing carbon black A and a crosslinking agent is incorporated into a rubber component and mixed to prepare an uncrosslinked rubber composition X'. This uncrosslinked rubber composition X' is then shaped and crosslinked to produce the wiper blade strip 10 described in the embodiment. Examples of molding methods include stamping, extrusion molding, injection molding, and transfer molding.

[0031] Example (Cross-linked rubber composition) The crosslinked rubber compositions of Examples 1-4 and Comparative Examples 1-6 were respectively configured as follows. The formulation of the uncrosslinked rubber compositions before crosslinking is also shown in Tables 1A and 1B.

[0032] <Example 1> Will be made by NR (Mounney viscosity: 60ML) 1+4 (100℃) and CR (thiol-modified, Mooney viscosity: 45~53ML)1+4 (100℃) A blend of rubbers mixed at a mass ratio of NR / CR=60 / 40 is used as the rubber component. Relative to 100 parts by mass of this rubber component, SRF (nitrogen adsorption specific surface area: 27m²) 2 The composition consists of 26 parts by weight of additives (66 nm / g, arithmetic mean particle size), and other additives are formulated and mixed according to Table 1 to prepare an uncrosslinked rubber composition. A crosslinked rubber composition obtained by crosslinking this uncrosslinked rubber composition is used as Example 1.

[0033] <Example 2> A blend of NR and CR in a mass ratio of NR / CR=55 / 45 was used as the rubber component. Otherwise, it was the same as in Example 1. A crosslinked rubber composition was prepared in this way, and this crosslinked rubber composition was used as Example 2.

[0034] <Example 3> The amount of SRF was set to 22 parts by mass relative to 100 parts by mass of rubber component. Otherwise, it was the same as in Example 1. The crosslinked rubber composition was prepared in this way and was used as Example 3.

[0035] <Example 4> The crosslinked rubber composition was prepared in accordance with the same procedure as in Example 3, except that N-tert-butyl-2-benzothiazole sulfenamide, which is used as sulfenamide vulcanization accelerator 2, was used instead of sulfenamide vulcanization accelerator 1. This crosslinked rubber composition is used as Example 4.

[0036] <Comparative Example 1> A blend of NR and CR in a mass ratio of NR / CR=50 / 50 was used as the rubber component, and the amount of SRF was set to 28 parts by mass relative to 100 parts by mass of the rubber component. Otherwise, it was the same as in Example 1. A crosslinked rubber composition was prepared in this way and this crosslinked rubber composition was used as Comparative Example 1.

[0037] <Comparative Example 2> A blend of NR and CR in a mass ratio of NR / CR=75 / 25 was used as the rubber component. Otherwise, it was the same as Comparative Example 1. A crosslinked rubber composition was prepared in this manner and this crosslinked rubber composition was used as Comparative Example 2.

[0038] <Comparative Example 3> The amount of SRF was set to 32 parts by mass relative to 100 parts by mass of rubber component. Otherwise, it was the same as in Example 1. The crosslinked rubber composition was prepared in this way and was used as Comparative Example 3.

[0039] <Comparative Example 4> The amount of SRF was set to 18 parts by mass relative to 100 parts by mass of rubber component. Otherwise, it was the same as Comparative Example 3. The crosslinked rubber composition was prepared in this way and was used as Comparative Example 4.

[0040] <Comparative Example 5> Using ISAF (Super Wear-Resistant Furnace Black), nitrogen adsorption specific surface area: 119m² 2 / g, arithmetic mean particle size: 22nm) instead of SRF, and its amount was set to 28 parts by mass relative to 100 parts by mass of rubber component. Otherwise, it was the same as Comparative Example 3. The crosslinked rubber composition was prepared in this way and was used as Comparative Example 5.

[0041] <Comparative Example 6> The amount of SRF was set to 28 parts by mass relative to 100 parts by mass of rubber component, and N-tert-butyl-2-benzothiazole sulfenamide, which is used as sulfenamide vulcanization accelerator 2, was used instead of sulfenamide vulcanization accelerator 1. Otherwise, it was the same as Comparative Example 3. The crosslinked rubber composition was prepared in this way and was used as Comparative Example 6.

[0042] [Table 1A]

[0043] [Table 1B]

[0044] (Experimental evaluation methods and results) The crosslinked rubber compositions in Examples 1-4 and Comparative Examples 1-6 were evaluated using the following tests. The test results are shown in Table 2.

[0045] <Permanent elongation at break> For the crosslinked rubber compositions in Examples 1-4 and Comparative Examples 1-6, the permanent elongation at tensile stress was measured at a standard test temperature (23±2℃) based on Japanese Industrial Standard JISK6273:2018.

[0046] <100% Modulus S 100 and 10% modulus S 10 > For the crosslinked rubber compositions in Examples 1-4 and Comparative Examples 1-6, the 100% modulus S was measured at the standard test temperature (23±2℃) based on Japanese Industrial Standard JIS K6251:2017. 100 and 10% modulus S 10 .

[0047] <Windshield wiper blade rubber strip test> A cross-linked rubber composition with the structure and characteristics described in Examples 1-4 and Comparative Examples 1-6 was prepared. Figure 1 Same wiper blade rubber strips.

[0048] Test pieces with a length of 5 cm were cut from wiper blade rubber strips formed from the crosslinked rubber compositions of Examples 1-4 and Comparative Examples 1-6. The mounting and holding portion of the wiper blade rubber strip test piece was mounted on a fixture, and the test piece was pressed against an aluminum plate, applying a pressing force of 16.7 N / m per unit length to the top surface of the lip. The test piece, in this state, was then placed in an oven at 80°C for 20 minutes. Next, the test piece was removed from the oven, and the pressing force on the aluminum plate was released. The gap extending along the thickness direction through the neck between the mounting and holding portion of the test piece and the lip had an angle due to the tilting of the lip; this angle was measured as the tilt angle.

[0049] [Table 2]

[0050] -Industry Applicability- This invention is useful in the technical field of wiper blade rubber strips.

[0051] - Symbol Explanation - 10. Wiper blade rubber strips 11 Installation and Holding Section 12. Lips 13 Neck 14. Edges.

Claims

1. A wiper blade rubber strip, formed from a cross-linked rubber composition containing rubber components and carbon black, characterized in that: The nitrogen adsorption specific surface area of ​​the carbon black is 20 m². 2 / g or more and 40m 2 / g or less The carbon black content in the crosslinked rubber composition is 15 parts by weight or more and less than 30 parts by weight relative to 100 parts by weight of the rubber component. The crosslinked rubber composition has a tensile permanent elongation of 12% or more and 18% or less, and the 100% modulus S of the crosslinked rubber composition is... 100 The crosslinked rubber composition has a 10% modulus S of 1.9 MPa or higher and 3 MPa or lower. 10 It is above 0.1 MPa and below 0.4 MPa.

2. The wiper blade rubber strip according to claim 1, characterized in that: The rubber component is a blend of natural rubber and chloroprene rubber.

3. The wiper blade rubber strip according to claim 2, characterized in that: The Mooney viscosity of the natural rubber is 50 ml. 1+4 (100℃ or above) and 80ML 1+4 (100℃) or less.

4. The wiper blade rubber strip according to claim 2 or 3, characterized in that: The chloroprene rubber is thiol-modified.

5. The wiper blade rubber strip according to any one of claims 2 to 4, characterized in that: The Mooney viscosity of the chloroprene rubber is 40 ml. 1+4 (100℃ or above) and 60ML 1+4 (100℃) or less.

6. The wiper blade rubber strip according to any one of claims 2 to 5, characterized in that: The content of natural rubber in the rubber component is greater than the content of chloroprene rubber in the rubber component.

7. The wiper blade rubber strip according to claim 6, characterized in that: The mass ratio of the natural rubber content in the rubber component to the chloroprene rubber content in the rubber component, NR / CR, is greater than 50 / 50 and less than 70 / 30.

8. The wiper blade rubber strip according to any one of claims 1 to 7, characterized in that: The carbon black contains semi-reinforcing furnace black.

9. The wiper blade rubber strip according to any one of claims 1 to 8, characterized in that: The crosslinked rubber composition contains sulfenamide vulcanization accelerators.

10. The wiper blade rubber strip according to claim 9, characterized in that: The sulfonamide-based vulcanization accelerator contains N-oxodiethyl-2-benzothiazole sulfonamide and / or N-tert-butyl-2-benzothiazole sulfonamide.

11. The wiper blade rubber strip according to any one of claims 1 to 10, characterized in that: The crosslinked rubber composition is formed by crosslinking with sulfur as a crosslinking agent.

Citation Information

Patent Citations

  • Hose with reinforced lug and its manufacture

    JP1982029877A

  • Analog signal comparator circuit

    JP1988071900A

  • Wiper blade

    JP2012140090A